Analysis the use of Audiovisual Hypnoteaching Learning Model in Improving Educational Results of Science Subject in Elementary School - Mayarni Mayarni; Isnaini Habsari; Rizkia Suciati; Gufron Amirullah; Susanti Murwatiningsih; Farha Nazilah (Postgraduate, University of Mataram, 2023)
This research aims to analyze the effectiveness of audiovisual hypnoteaching learning models given in science learning at SDN Jatiranggon II Bekasi for the 2021/2022 academic year. This study consists of qualitative experimental research using nonequivalent control group design. The test subjects involved 25 students from class IV A as the control class and 26 students from class IV B as the experimental class. Pretest–posttest techniques are used to collect data in each class and the data was quantitatively analyzed. The results of using the audiovisual hypnoteaching learning model on force material obtained an N-Gain score of 0.65 in the control class and an N-Gain score of 0.80 in the experimental class with very high category. The pretest–posttest results of the control class and experimental class are normal. In conclusion, the fourth-grade students' achievement in science on force material are significantly impacted by the audiovisual-based hypnoteaching model.